Geology and landscape evolution : general principles applied to the United States - DiPietro, Joseph A., 1957- (Elsevier, 2018)
Geology and Landscape Evolution: General Principles Applied to the United States, Second Edition, is an accessible text that balances interdisciplinary theory and applications within the physical geography, geology, geomorphology and climatology of the United States. The vast diversity of terrain and landscape across the United States makes this an ideal tool for geoscientists worldwide who research the country's geological and landscape evolution. The book provides an explanation of how landscape forms, how it evolves and why it looks the way it does. This new edition is fully updated with greater detail throughout and additional figures, maps, drawings and photographs. Rather than limiting the coverage specifically to tectonics or to the origin and evolution of rocks with little regard for the actual landscape beyond general desert, river and glacial features, this book concentrates specifically on the origin of the landscape itself, with specific and exhaustive reference to examples from across the United States.